An open‐label phase I/II study of cyclophosphamide, bortezomib, pegylated liposomal doxorubicin, and dexamethasone in newly diagnosed myeloma. (12th March 2015) - Nishihori, Taiga; Baz, Rachid; Shain, Kenneth; Kim, Jongphil; Ochoa‐Bayona, Jose L.; Yue, Binglin; Sullivan, Daniel; Dalton, William; Alsina, Melissa
Abstract We conducted a phase 1/2 trial evaluating the combination of cyclophosphamide, bortezomib, pegylated liposomal doxorubicin, and dexamethasone (CVDD) for newly diagnosed multiple myeloma (MM). The primary objective of the phase 1 was to evaluate the safety and tolerability of maximum planned dose (MPD) and the phase 2 was to assess the overall response rate. Patients received 6–8 cycles of CVDD at four dose levels. There were no dose‐limiting toxicities. The MPD was cyclophosphamide 750 mg/m2 IV on day 1, bortezomib 1.3 mg/m2 IV on days 1, 4, 8, 11, pegylated liposomal doxorubicin 30 mg/m2 IV on day 4, and dexamethasone 20 mg orally on the day of and after bortezomib (21‐d cycle). Forty‐nine patients were treated at the MPD of which 22% had high‐risk myeloma. The most common grade ≥3 toxicities included myelosuppression, infection, and fatigue. Overall response and complete response rates were 91% and 26% in standard‐risk, and 100% and 58% in high‐risk cohort, respectively. After a median follow‐up of 34 months, the median progression‐free survival was 31.3 months. The 2‐yr overall survival was 91.1% in the standard‐risk and 88.9% in the high‐risk cohort, respectively. CVDD regimen was well tolerated and was highly active in newly diagnosed MM.